Colonial Geographies, Black Geographies, and Bioethics - Mccurdy, Jennifer (The Hastings Center report, 2022)
Structural anti-Black racism exists within the fields of bioethics and medicine. The colonial structures underlying bioethics render the geographies and subjectivities of Black scholars and patients "ungeographic," hidden by dominant White geographies. In this essay, I aim to illuminate more clearly the anti-Black racist structures embedded in bioethics and medicine by engaging with Katherine McKittrick's work Demonic Grounds: Black Women and the Cartographies of Struggle. Specifically, I apply McKittrick's concepts of Black geographies to the physical spaces of health care (which could be the hospital, intensive care ward, or birthing room) and the discursive space of bioethics journals and texts. Finally, recommendations are made for bioethics to build the capacity to hold a multiplicity of geographies simultaneously.